Ikona, świadek, ofiara. Niedźwiedź polarny jako figura wizualna dyskursu zmiany klimatu - Piasecki, Michał (Zagadnienia Rodzajów Literackich, 2021)
The article focuses on the media practice of using visual representations of polar bears to illustrate information about climate change. It starts with a short description about the iconic status that climate discourse attributes to these type of images. The article addresses the question about how this iconic status is defined and what the media specificity of the polar bear is as a part of “charismatic megafauna.” These iconic properties are placed in contexts related to communicating issues related to climate change, and as a consequence the article emphasises the subsequent disappointment that these kind of representations have brought about. To begin with the article focuses on a reconstruction of the images of polar bears that were created at a time when it became a species in danger of extinction. Subsequently, the article characterizes the representations of the species in relation to the effects of climate change. The analysis refers to the typology proposed by Dorothea Born, who suggested that three types of such representations are namely: “anthropomorphized bears,” “bear in context,” “bear in danger.” Finally, the focus turns to the victimising dimension of these representations. When seen from the perspective of the polar bear as a victim, there is a need to emphasize the role of the suffering body, which can be seen as a common denominator in the human-non-human condition of vulnerability.